1962
DOI: 10.1055/s-0028-1111892
|View full text |Cite
|
Sign up to set email alerts
|

Die Thalidomid-Embryopathie*

Abstract: Im Oktober 1960 haben Kosenow und Pfeiffer auf der Tagung der Deutschen Gesellschaft für Kinderheilkunde in Kassel Räntgenbilder i.md Fotografien von zwei Säuglingen mit Aplasie der Daumen, der Radii und der Tibiae, Duodenalstenose und kapillärem Häthangiom der Oberlippe demonstriert. Einer hatte außerdem eine Femuraplasie. Ansctheinend war keinem der Anwesenden, audi den erfahrensten Pädiatern nicht (z. B. Fanconi), dies neue Syndrom bekannt. Wiedemann lenkte knapp ein Jahr später die Aufmerksamkeit der Ärzte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
9

Year Published

1965
1965
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(58 citation statements)
references
References 0 publications
0
49
0
9
Order By: Relevance
“…In addition to congenital heart defects, damage occurred to the ocular structures, cranial nerves, ears, kidneys, intestines, and genitalia. Lenz and others suggested a possible correlation with thalidomide taken during pregnancy (McBride, 1961;Lenz, 1962;Lenz and Knapp, 1962;Smithells, 1962). Within a few years the drug was withdrawn from commercial sale in most countries, but not before over 5000 cases of malformed live births occurred worldwide.…”
Section: Thalidomide: Historicalmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to congenital heart defects, damage occurred to the ocular structures, cranial nerves, ears, kidneys, intestines, and genitalia. Lenz and others suggested a possible correlation with thalidomide taken during pregnancy (McBride, 1961;Lenz, 1962;Lenz and Knapp, 1962;Smithells, 1962). Within a few years the drug was withdrawn from commercial sale in most countries, but not before over 5000 cases of malformed live births occurred worldwide.…”
Section: Thalidomide: Historicalmentioning
confidence: 96%
“…Within a few years the drug was withdrawn from commercial sale in most countries, but not before over 5000 cases of malformed live births occurred worldwide. Since the survival rate of thalidomide-exposed children is between 40 and 50%, it has been estimated that more than 10,000 pregnancies may have been affected (Lenz, 1962;Lenz and Knapp, 1962;Lenz, 1966Lenz, , 1988.…”
Section: Thalidomide: Historicalmentioning
confidence: 99%
“…3), information was obtained from current literature on embryonic development and from data collected in the early 1960s from mothers who had given birth to children with thalidomide embryopathy [Lenz and Knapp, 1962;Nowack, 1965]. It was found that thalidomide has an early and narrow teratogenic time period during days 20 to 36 post fertilization (pf) and that the different malformations are induced during specific and very short time periods.…”
Section: Timingmentioning
confidence: 99%
“…In the initial reports of thalidomide embryopathy, a timetable for the critical time periods during pregnancy, when the malformations were produced, was set up [Lenz and Knapp, 1962;Nowack, 1965]. Utilizing this information, it would be possible to compare the multiple anomalies in CA with those occurring in thalidomide embryopathy and suggest specific time periods for the development of the malformations.…”
Section: Introductionmentioning
confidence: 99%
“…These three babies subsequently died from atresia of the bowel in spite of operative attempts to relieve the condition. 4 Only in the rabbit has an analogous correspondence been regularly demonstrated between the animal and the human deformity (Figure 1). * In 1961 Somers in England reported the production of limb deformities in the offspring of New Zealand rabbits fed thalidomide during the [8][9][10][11][12][13][14][15][16] days of pregnancy, a finding which has been confirmed several times.…”
Section: Implications Of Epidemic Embryopathy For Public Healthmentioning
confidence: 99%